STUDI PERBANDINGAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP PEMUSNAHAN BARANG SELUDUPAN DI KOTA SABANG - Muzakkir Muzakkir (STISNU Aceh, 2022)
This study focuses on a comparative study of Islamic law and positive law on the destruction of contraband in the city of Sabang, while the aim is to find out the process of confiscating contraband in the city of Sabang and to find out the views of Islamic law and positive law on the destruction of contraband. This study is a literature review and field study using qualitative methods. Data collection was carried out by studying books and books on Islamic law and positive law as well as interviews and documentation. The results of the study show that the illegal confiscation process at Sabang City Customs and Excise was carried out through information from the public, after the information has been collected and deemed sufficient, a search will be carried out at the location, if a suspicious movement is found, a search will be carried out and if it is found, it will be confiscated and interviewed the owner about the origin of ownership of the goods. Whereas in a review of Fatwa MPU Aceh No. 1 of 2014 concerning the Destruction of Illegal Goods in the Perspective of Islamic Law it is explained that the destruction of smuggled goods is seen from two aspects, if the goods are goods that are not useful, then they are required to be destroyed, and if the goods are smuggled are goods that are useful or can be used for the needs of the community, then it is forbidden to destroy them. Whereas in a positive legal review regarding smuggled goods whether useful or not, it is justified to be destroyed. This is in accordance with what is regulated in Law No. 17 of 2006 concerning Customs and Excise